Dielectrophoresis and AC electroosmosis force on fluid motion in microfluidic using latex particles - Md Yunus, Nurul Amziah; Mohtar, Mohd Nazim; Almadhagi, Khaldon Mohammed; Abdul Halin, Izhal (Universiti Putra Malaysia Press, 2017)
The use of electroosmotic is fast becoming a proven technique for manipulating particles in microfluidic systems. Several approaches were experimented to improve the force and thus the moving particles in the fluid. This paper will study the effect of microelectrode on the moving particles in latex using a particle image velocimetry and to test the velocity of particles movement at various frequencies from 10 kHz to 500 kHz. The result shows the behaviour of latex particles at different frequencies varying from low frequencies up to high frequencies under AC electrokinetic forces such as dielectrophoresis (DEP) and AC electroosmosis (ACEO).